Applying the Kaizen Management System in the Manufacturing Process of Artistic Products in Handicraft Workshops - Rahmanpour, Nahid (International Journal of Engineering and Technology, 2018)
Being knowledge-based, handicrafts-manufacturing workshops established by art graduates are to design and manufacture innovative products in line with modern lifestyle. Unfortunately, such workshops are often encountered with challenges due to lacking the use of a specific management system in their production and supply processes. For this purpose, the application of Kaizen’s management system was discussed in the present study because of its ease of implementation, high effectiveness of results, low costs, and emphasis on teamwork in the production of handicrafts. This study was applied in terms of the research purpose with a descriptive survey design. The statistical population of the study included 17 handicrafts-manufacturing workshops established by art graduates in the last fifteen years. The results of this study showed that the application of Kaizen’s management system and its operational procedures could provide conditions for continuous improvement in the production process of handicrafts, reduce the cost and time of production, increase quality, and enhance delivery performance.